Demand for credit, international financial legitimacy, and vulnerability to crises: Regulatory change and the social origins of Iceland's collapse. Issue 2 (19th November 2013) - Larson, Erik
Abstract: By analyzing how credit in Iceland expanded to culminate in the country's 2008 financial collapse, this article advances theories about financial crises, regulatory change, and the role of credit. It also complicates popular accounts of Iceland's collapse that focus on the actions of unrestrained bankers by examining the larger context that facilitated these banking practices. After financial liberalization, Icelandic businesses and households had strong demand for credit as a result of: (i) the institutional meaning of credit, (ii) an emergent growth strategy of aggressive international expansion, and (iii) increasing consumption. Incorporating business demand for credit extends demand‐side theory of crises and shows how dominant strategy and shared government and business orientation toward opportunity shaped credit expansion. Credit‐based consumption also stabilized social relations despite increasing inequality. Notwithstanding warnings of risk, regulation did not restrain risky leverage. International market reactions reinforced beliefs about Icelandic success to limit regulatory reach, as Iceland's international financial legitimacy produced market‐based measures that leaders interpreted as signals of economic success.